2014
DOI: 10.1158/1940-6207.capr-14-0143
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Vitamin B12 May Play a Critical Role in Lowering the HPV 16 Methylation–Associated Risk of Developing Higher Grades of CIN

Abstract: We previously reported that a higher degree of methylation of CpG sites in the promoter (positions 31, 37, 43, 52 and 58) and enhancer site 7862 of HPV 16 was associated with a lower likelihood of being diagnosed with HPV 16-associated CIN 2+. The purpose of the current study was to replicate our previous findings and in addition to evaluate the influence of plasma concentrations of folate and vitamin B12 on the degree of HPV 16 methylation (HPV 16m). The study included 315 HPV 16 positive women diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 20 publications
2
36
0
2
Order By: Relevance
“…Flatley' study showed that a low folate level increased the risk of cervical cancer 30. Moreover, Piyathilake recently reported that folate and vitamin B12 may play critical roles in lowering the HPV16 methylation-associated risk of developing higher grades of CIN 31. Consistent with these findings, our data indicate that a low dietary folate intake may be a regional risk factor for increased CIN incidence in this area.…”
Section: Discussionsupporting
confidence: 87%
“…Flatley' study showed that a low folate level increased the risk of cervical cancer 30. Moreover, Piyathilake recently reported that folate and vitamin B12 may play critical roles in lowering the HPV16 methylation-associated risk of developing higher grades of CIN 31. Consistent with these findings, our data indicate that a low dietary folate intake may be a regional risk factor for increased CIN incidence in this area.…”
Section: Discussionsupporting
confidence: 87%
“…Higher folate levels protected against HPV infections and were associated with eradicating infection in HPV‐positive women in a 2‐year prospective study . Folate and vitamin B12 at high concentrations independently protect against the development of CIN‐2 and CIN‐3, possibly through methylation of the HPV E6 promoter and enhancer, which is involved in cervical carcinogenesis …”
Section: Risk Factors and Protective Factorsmentioning
confidence: 99%
“…51 Folate and vitamin B12 at high concentrations independently protect against the development of CIN-2 and CIN-3, possibly through methylation of the HPV E6 promoter and enhancer, which is involved in cervical carcinogenesis. 52 In addition, specific cervical microbial profiles are associated with the risk of CIN 2 or greater, suggesting the usefulness of combined approaches, including probiotics and vitamin supplementation along with vaccination (reviewed below), to reduce the overall risk of cervical cancer. 53…”
Section: Risk Factors and Protective Factorsmentioning
confidence: 99%
“…Piyathilake и соавт. (2014) пришли к выводу, что персистенция ВПЧ и развитие CIN и РШМ зави-сят от метилирования ДНК самого вируса [12]. Пол ноце н но е ме т и л и р ов ание ДНК ВПЧ после внедрения в клетку способствует подавлению синтеза его онкобелков.…”
Section: фолатный статус и развитие цервикальных дисплазийunclassified
“…Метилирование генома ВПЧ-16 зависит от уровня фолатов как донаторов метильной группы и ведет к значительному подавлению синтеза онкобелков (в частности, Е6). Достижение оптимального уровня фолатов может приводить к снижению экспрессии генов онкобелков в клетках, инфицированных ВПЧ [12]. Позже в экспериментальной работе (2018), где изучалось влияние уровня фолатов на геномную интеграцию ДНК ВПЧ-16 in vivo на новой мышиной модели для быстрой онкогенной трансформации кератиноцитов человека, S. Xiao и соавт.…”
Section: фолатный статус и развитие цервикальных дисплазийunclassified